(untitled) (Research, Society and Development, 2022)
Bacterial resistance to antimicrobials is one of the major challenges for public health today. An important concern is food provided in a hospital environment, due to its ability to transmit antimicrobial resistance genes. This study aimed to evaluate antimicrobial resistance, and characterize the resistance genes of gram-negative bacteria in the microbiota of cheese samples served to patients admitted to a public hospital in Rio de Janeiro. This research used a methodology to capture the Gram-negative microbiota resistant to antimicrobials. The disk diffusion test and the polymerase chain reaction (PCR) were performed to investigate, respectively, the phenotypic and genotypic resistance of Gram-negative bacteria to the tested antimicrobials. The microbiota of all cheese samples showed high phenotypic resistance. In 62.5% of the samples, resistance reached more than nine tested antimicrobials. Five antimicrobials did not show susceptibility in 100% of the samples analyzed. With the exception of the antimicrobial ciprofloxacin, resistance percentages above 62% were found in all samples, including fourth-generation cephalosporin. All cheese samples harbored resistance genes. Seven different resistance genes were found in 34 microbiota of Gram-negative bacteria, namely: int-1, int-2, ctx, shv, tem, tetA and tetB. We conclude the alarming presence of potentially antimicrobial-resistant genes in cheeses served to cancer patients, indicating that this food may be a carrier of bacteria with resistance genes in a hospital environment.